Accrual Accounting and the Local Government Budget - A Matching Evaluation - Christian Raffer (ZBW - Leibniz Information Centre for Economics, 2020)
The transition from cash to accrual accounting is said to change a government's perception of its budget quite fundamentally. Although an exorbitant number of governments have reformed the mode of accounting at high costs in past years, reliable empirical evidence of consequences on their financial situation and decision-making is still scarce. In this paper, budget variables are analysed which are hypothesized to react to the reform: investment expenditure and revenue from asset sales. Microdata from 1,100 local governments in the German state of Baden-Württemberg over the period 2005-2016 is exploited with different matching techniques combined with the conditional DiD estimator. Results imply a robust effect on municipal investment behaviour and indicate an impact on sales revenue. This corroborates the latest empirical results. This not only provides external validation. For the first time a common understanding of the budgetary effects of the accrual accounting reform based on econometric analyses seems to be emerging.
Keywords: H72; H83; M41; 330; Accrual Accounting; Propensity Score Matching; Public Finance